Designare: pontes artístico/educativas na formação docente em Artes Visuais - Vasconcelos, Flávia Maria de Brito Pedrosa (2015)
This is a thesis that search to build an interpretation of the Drawing and its teaching in the Visual Arts Teachers Education, questioning the "know how to draw" and "did not know how to draw" in the view of teachers who teach in this area on higher level. I discuss these issues in building a view at visual and written narrative about speeches found in philosophical and historical approaches to teaching Visual Arts. By combining three research methodologies for Educational Research Based on Visual Arts (Viadel, 2005), the narrative, the Autoethnography and the A/ r/tography and research literature, questioning and building a justificative in and narrative from memories, interviews with teachers who teach Drawing at higher level courses in the field of Visual Arts at the University of Porto - UPorto and the Federal University of São Francisco Valley - UNIVASF, I analyze the spaces of artistic education in the formation of the Visual Arts teacher, attentive to discourses and practices of teachers in the investigated contexts. Finally, I reflect on the pathways developed in research and highlight the relevance of the Drawing and its teaching in contemporaneity, suggesting indicative points and work possibilities, with reference to the need for a critical/reflective construction of the artistic/educative designare between experiential bridges.